2021
DOI: 10.1161/strokeaha.120.031622
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Determined Smoking Behavior and Risk of Nontraumatic Subarachnoid Hemorrhage

Abstract: Background and Purpose: Animal and observational studies indicate that smoking is a risk factor for aneurysm formation and rupture, leading to nontraumatic subarachnoid hemorrhage (SAH). However, a definitive causal relationship between smoking and the risk of SAH has not been established. Using Mendelian randomization (MR) analyses, we tested the hypothesis that smoking is causally linked to the risk of SAH. Methods: We conducted a 1-sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In a case–control study including 4701 patients with 6411 IAs, the authors found that current cigarette smoking, smoking intensity, and smoking duration were significantly associated with ruptured IAs at presentation 4 . A recently published MR study using data from the UK Biobank also showed a causal relationship between smoking and SAH 12 . This MR study provided genetic evidence for the causal relationship between smoking and IA.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In a case–control study including 4701 patients with 6411 IAs, the authors found that current cigarette smoking, smoking intensity, and smoking duration were significantly associated with ruptured IAs at presentation 4 . A recently published MR study using data from the UK Biobank also showed a causal relationship between smoking and SAH 12 . This MR study provided genetic evidence for the causal relationship between smoking and IA.…”
Section: Discussionmentioning
confidence: 88%
“…Above-mentioned confounding and reverse causation are avoided in MR studies since genetic alleles are randomly assorted during conception 10 . Limited evidence from MR for ICAs has been reported 11 , 12 . A MR study using the data from UK-Biobank showed a causal link between smoking and the risk of SAH 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other MR studies, Larsson et al (2019aLarsson et al ( , 2020c confirmed the association between smoking initiation and the risk of any ischemic stroke, LAS and SVS, but did not find an association with cardioembolic stroke (CES) or ICH. In a one-sample MR study using the UK Biobank, Acosta et al (2021) confirmed an association between genetic propensity to smoke and risk of nontraumatic subarachnoid hemorrhage.…”
Section: Smokingmentioning
confidence: 83%
“…It has been realized by more and more neurosurgeons that environmental factors act a more significant role than inherited factors in the pathophysiology of IAs [ 15 , 16 ]. Pyysalo et al have reported the association of IAs with oral bacteria, suggesting a link between aneurysms and bacteria [ 17 ].…”
Section: Discussionmentioning
confidence: 99%